Human outbreak of St. Louis encephalitis detected in Argentina, 2005 - Spinsanti, Lorena Ivana (2008)
Background: An outbreak of flavivirus encephalitis occurred in 2005 in Córdoba province, Argentina. Objectives: To characterize the epidemiologic and clinical features of that outbreak and provide the serologic results that identified St. Louis encephalitis virus (SLEV) as the etiologic agent. Study design: From January to May 2005, patients with symptoms of encephalitis, meningitis, or fever with severe headache were evaluated and an etiologic diagnosis achieved by detection of flavivirus-specific antibody sera and cerebrospinal fluid. Results: The epidemic curve of 47 cases showed an explosive outbreak starting in January 2005 with one peak in mid-February and a second peak in mid-March; the epidemic ended in May. Cases occurred predominantly among persons 60 years and older. Nine deaths were reported. SLEV antibodies, when detected in 47 patients studied, had a pattern characteristic of a primary SLEV infection. Conclusions: Even though isolated cases of St. Louis encephalitis have been reported in Argentina, this is the first description of a large SLEV encephalitis outbreak in Argentina.